Fibroblast Growth Factor 23 in Feline Chronic Kidney Disease. (11th February 2013) - Geddes, R.F.; Finch, N.C.; Elliott, J.; Syme, H.M.
<x xml:space="preserve">Abstract</x> Background Fibroblast growth factor 23 (FGF‐23) is a phosphaturic hormone involved in the pathogenesis of secondary renal hyperparathyroidism (SRHP) in humans. There are no published studies examining feline FGF‐23. Objectives Validation of a method for FGF‐23 quantification in feline plasma and assessment of the associations among plasma FGF‐23, PTH, creatinine, and phosphate concentrations in cats with chronic kidney disease (CKD). Animals One hundred nonazotemic and azotemic geriatric (>9 years) client‐owned cats. Methods Retrospective cross‐sectional study: Cats were categorized into 4 groups: control group (plasma creatinine (Cr) ≤2.0 mg/dL), stage 2 (Cr 2.1–2.8 mg/dL), stage 3 (Cr 2.9–5.0 mg/dL), stage 4 (Cr >5.0 mg/dL). Stages 2 and 3 were further subdivided based on International Renal Interest Society targets for plasma phosphate concentration (PO4): stage 2a (PO4 ≤4.5 mg/dL), stage 2b (PO4 >4.5 mg/dL), stage 3a (PO4 ≤5 mg/dL), stage 3b (PO4 >5 mg/dL). Plasma FGF‐23 concentrations were measured by a human intact FGF‐23 ELISA. Descriptive statistics and linear regression were performed. Results The ELISA demonstrated acceptable precision, reproducibility, and specificity. Plasma FGF‐23 concentrations increased with increasing plasma creatinine concentrations and were significantly different between all groups (P < .008). Plasma FGF‐23 concentrations were significantly higher in cats in stage 2b than stage 2a (P = .008) and in stage 3b than in stage 3a (P = .012). Phosphate, log creatinine, total calcium, log parathyroid hormone, and packed cell volume were all independent predictors of FGF‐23. Conclusions and Clinical Importance FGF‐23 concentrations increase with increasing stage of feline CKD and might be a marker or mediator of feline SRHP.